Typification and identity of five taxa of Peliosanthes (Asparagaceae), with proposal of the new name P. pumila for P. violacea var. minor - Tanaka, Noriyuki (Phytotaxa, 2019)
Lectotypes are designated for Peliosanthes campanulata (basionym: Lourya campanulata), P. courtallensis and P. neilgherrensis, and determined for two varieties of P. violacea, P. violacea var. violacea and P. violacea var. minor, which were dually lectotypified in previous papers. Peliosanthes violacea var. minor is regarded as a distinct species and named P. pumila.